Effectiveness of Open University Website as Administration and Academic Dissemination Media to UPBJJ-UT Mataram Students - Windi Prihandoyo (Budapest International Research and Critics University, 2022)
This study aimed to identify and analyze the effectiveness of Open University Website as administrative and academic information dissemination media to UPBJJ-UT Mataram students. The method used in this study was a descriptive correlational survey. This research was conducted at UPBJJ-UT Mataram, West Nusa Tenggara Province. Theresults indicated that student characteristics andthe quality of interaction withOpen University websitehad positive but insignificant relationship with the effectiveness of Open University website as a medium for dissemination of administrative and academic information at UPBJJ-UT Mataram. Furthermore, the usability of the Open University website and the quality of website information showed significantly positive relationship with the effectiveness of the Open University website as a medium for dissemination of administrative and academic information at UPBJJ-UT Mataram.